Hole transport material, preparation method thereof and perovskite solar cell

By introducing thiophene-methoxytrianilin groups and thiophene-methylthiotrianilin groups into the acridine phosphate side chain, a new hole transport material was developed, which solved the problems of high cost of hole transport materials, low decomposition temperature and low hole mobility in the prior art, and significantly improved the performance of perovskite solar cells.

CN119504859AActive Publication Date: 2025-02-25JINKO SOLAR (SHANGRAO) CO LTD +1

Patent Information

Application Number
CN202411667997.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

In the prior art, hole transport materials have problems such as high raw material cost, low decomposition temperature and low hole mobility.

Method used

By introducing thiophene-methoxytrianilin groups and thiophene-methylthiotrianilin groups to the acridinium phosphate side chain, a novel hole transport material is provided, which has good solubility, film formation and hole mobility in a variety of solvents, and has high decomposition temperature and thermal stability.

Benefits of technology

The hole transport material can improve the photoelectric conversion efficiency, photovoltaic performance and stability of perovskite solar cells, and is repeatable without doping additives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504859A_ABST
    Figure CN119504859A_ABST
Patent Text Reader

Abstract

The invention provides a hole transport material, a preparation method thereof and a perovskite solar cell. The chemical structural formula of the hole transport material is # imgabs0 #, wherein each A is independently a heteroatom. A thiophene-methoxy triphenylamine group and a thiophene-methylthio triphenylamine group are introduced into an acridine phosphate side chain, and a series of novel hole transport materials are provided. The hole transport material has higher decomposition temperature, better thermal stability and higher hole mobility, thereby being beneficial to hole extraction and transport. The hole transport material has a deep HOMO energy level matched with perovskite, and can be used in a perovskite solar cell without doping any additive, so that the perovskite solar cell has higher photoelectric conversion efficiency, photovoltaic performance and stability, and the material has repeatability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic technology, and in particular to a hole transport material and a preparation method thereof, and a perovskite solar cell. Background Art

[0002] Perovskite solar cells (PSCs) are devices that use perovskite-type organic metal halide semiconductors as light-absorbing materials to directly convert light energy into electrical energy through the photovoltaic effect. Among them, trans-structured PSCs show great potential in commercial applications. The continuous development of new hole transport materials (HTMs) is a key factor in the preparation of efficient and stable perovskite solar cells. Polymer hole transport materials have great potential in the realization of large-area trans-perovskite solar cells due to their excellent film-forming properties and solvent resistance.

[0003] In inverse perovskite solar cells, hole transport materials, as important transport layer materials between the perovskite layer and the transparent electrode, are not only responsible for the extraction and transport of holes and blocking the flow of electrons, but also directly affect the crystallization and film-forming properties of perovskite, playing a decisive role in improving battery performance and realizing large-scale commercial applications. Summary of the invention

[0004] The main purpose of the present invention is to provide a hole transport material and a preparation method thereof, and a perovskite solar cell, so as to solve the problems of high raw material cost, low decomposition temperature and low hole mobility of hole transport materials in the prior art.

[0005] In order to achieve the above object, according to one aspect of the present invention, a hole transport material is provided, the chemical structure of which is wherein each A is independently a heteroatom.

[0006] Furthermore, each of the above A is independently O or S.

[0007] Furthermore, the decomposition temperature of the hole transport material is 298 to 345° C.; and / or the HOMO energy level of the hole transport material is -5.39 to -5.32 eV; and / or the hole mobility of the hole transport material is 3.67×10 -4 ~6.35×10 -4 cm 2 ·V -1 ·S -1 .

[0008] According to another aspect of the present invention, a method for preparing the aforementioned hole transport material is provided, the method comprising: step S1, under the protection of an inert gas, The raw materials are mixed and subjected to the first substitution reaction to generate Step S2, under the protection of inert gas, includes The raw materials of trimethylsilyl bromide and 1,4-dioxane are mixed and subjected to a first reaction to obtain an intermediate; step S3, under the protection of an inert gas, the raw materials including the intermediate, methanol and water are mixed and subjected to a second reaction to obtain Wherein, A is a heteroatom.

[0009] Furthermore, in the above step S1, Each A in is independently O or S.

[0010] Furthermore, the raw materials in the above step S1 also include tetrakis(triphenylphosphine)palladium, potassium carbonate, toluene, ethanol and water; and / or, The molar ratio of potassium carbonate to tetrakis(triphenylphosphine)palladium is 1:2.2-2.5:4-6:0.05-0.1; and / or, the temperature of the first substitution reaction is 85-90° C.; and / or, the time of the first substitution reaction is 6-12 hours.

[0011] Furthermore, the temperature of the first reaction is 25-30° C.; and / or, the time of the first reaction is 12-16 hours; and / or, the temperature of the second reaction is 25-30° C.; and / or, the time of the second reaction is 12-16 hours; and / or, The molar ratio of trimethylsilyl bromide to trimethylsilyl bromide is 1:10-20.

[0012] Furthermore, the above The preparation method comprises: step S11, comprising After mixing with the raw material of N-bromosuccinimide, bromination reaction is carried out to obtain Step S12 includes The raw materials of tetrabutylammonium bromide, dibromobutane and potassium hydroxide are mixed and subjected to a second substitution reaction to obtain Step S13 includes After mixing with the raw material of triethyl phosphite, a third substitution reaction is carried out to obtain

[0013]

[0014] Furthermore, the raw material in the above step S11 also includes tetrahydrofuran, The molar ratio of the amount of N-bromosuccinimide is 1:2.5-3; and / or, the temperature of the bromination reaction is 0-5°C; and / or, the time of the bromination reaction is 12-18h; and / or, in step S12, The molar ratio of tetrabutylammonium bromide to potassium hydroxide is 1:0.1-0.2:7-10; and / or, the temperature of the second substitution reaction is 65-85°C; and / or, the time of the second substitution reaction is 12-24h; and / or, in step S13, The molar ratio of the third substitution reaction to triethyl phosphite is 1:25-50; and / or the temperature of the third substitution reaction is 140-150° C.; and / or the time of the third substitution reaction is 12-24 hours.

[0015] According to another aspect of the present invention, a perovskite solar cell is provided, comprising a transparent conductive layer, a hole transport layer, a perovskite layer, an electron transport layer and an electrode layer, wherein the hole transport layer is composed of the aforementioned hole transport material.

[0016] By applying the technical solution of the present invention, the present application introduces thiophene-methoxy triphenylamine groups and thiophene-methylthio triphenylamine groups into the acridine phosphate side chain, and provides a series of novel hole transport materials, which have good solubility in solvents such as dimethyl sulfoxide, N, N' dimethylformamide, toluene, chlorobenzene and dichloromethane. The material has good film-forming properties, and has good wettability with perovskite precursor solvents, thereby helping to improve the crystallinity and film-forming properties of perovskite. And this type of hole transport material has a higher decomposition temperature, better thermal stability and higher hole mobility, which is conducive to the extraction and transmission of holes. This type of hole transport material has a deeper HOMO energy level that matches perovskite, and it can be used in perovskite solar cells without doping any additives, so that the perovskite solar cell has higher photoelectric conversion efficiency, photovoltaic performance and stability, and the material has repeatability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0018] Figure 1 shows the hydrogen nuclear magnetic resonance spectrum of the hole transport material in Example 1 of the present application;

[0019] Figure 2 shows the hydrogen nuclear magnetic resonance spectrum of the hole transport material in Example 2 of the present application;

[0020] Figure 3 A schematic diagram of the structure of a perovskite solar cell of the present application is shown.

[0021] The above drawings include the following reference numerals:

[0022] 1. Transparent conductive layer; 2. Hole transport layer; 3. Perovskite layer; 4. Electron transport layer; 5. Electrode layer. DETAILED DESCRIPTION

[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0024] Currently, some of the most promising inverted perovskite solar cells are made of self-assembled monolayers (SAMs) containing carbazole phosphoric acid (PA), such as [2-(9H-carbazole-9-yl)ethyl]phosphate (2PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphate (MeO-2PACz), and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphate (Me-4PACz). They have the ability to coat evenly on rough surfaces, high hole extraction selectivity, and low interface electron trap density, so they can be used as excellent hole-selective contact layers. At the same time, HTMs containing triphenylamine (TPA) have good thermal and morphological stability, as well as good charge transport and ionization potential. The most effective common method for constructing HTMs is still methoxy-substituted diphenylamine or triphenylamine. At present, HTMs in perovskite solar cells are mainly divided into three categories: inorganic hole transport materials, organic small molecule hole transport materials and organic polymer hole transport materials. Small molecule HTMs have a clear structure and molecular weight. According to the spatial structure, they can be roughly divided into three categories: linear structure, spirocyclic structure and star structure. They can also be divided into dithienylpyrrole type, triphenylamine type, carbazole type, bifluorene type, thiophene type, etc. according to the different groups contained in the molecular structure. Small molecule HTMs have become the most common type of HTMs in perovskite solar cells due to their synthetic varieties, adjustable properties, high purity and easy solution processing. However, due to their rigid structure, they have low tolerance to perovskite precursor solutions. The films produced by small molecule HTMs always have pinhole morphological defects and are unstable in morphology under external stimulation. In addition, many small molecule HTMs require the addition of dopants. These factors will also bring obstacles to the large-scale commercialization of PSCs. As analyzed in the background technology of this application, hole transport materials in the prior art have problems such as high raw material cost, low decomposition temperature and low hole mobility. In order to solve the above problems, this application provides a hole transport material and a preparation method thereof, and a perovskite solar cell.

[0025] In a typical embodiment of the present application, a hole transport material is provided, the chemical structure of which is wherein each A is independently a heteroatom.

[0026] The present application introduces thiophene-methoxy triphenylamine groups and thiophene-methylthio triphenylamine groups into acridine phosphate side chains to provide a series of novel hole transport materials, which have good solubility in solvents such as dimethyl sulfoxide, N,N' dimethylformamide, toluene, chlorobenzene and dichloromethane. The material has good film-forming properties, and has good wettability with perovskite precursor solvents, thereby helping to improve the crystallinity and film-forming properties of perovskite. And this type of hole transport material has a higher decomposition temperature, better thermal stability and higher hole mobility, which is conducive to the extraction and transmission of holes. This type of hole transport material has a deeper HOMO energy level that matches perovskite, and it can be used in perovskite solar cells without doping any additives, so that perovskite solar cells have higher photoelectric conversion efficiency, photovoltaic performance and stability, and the material has repeatability.

[0027] In order to further improve the solubility, film-forming property and hole mobility of the hole transport material, in one embodiment of the present application, each of the above A is independently O or S, and optionally all A are O or all A are S.

[0028] In one embodiment of the present application, the decomposition temperature of the hole transport material is 298 to 345°C; and / or the HOMO energy level of the hole transport material is -5.39 to -5.32 eV; and / or the hole mobility of the hole transport material is 3.67×10 -4 ~6.35×10 -4 cm 2 ·V -1 ·S -1 .

[0029] Applying hole transport materials with the above-mentioned decomposition temperature, HOMO energy level and hole mobility range to perovskite solar cells will help to further improve the photoelectric conversion efficiency, photovoltaic performance and stability of perovskite solar cells.

[0030] In another typical embodiment of the present application, a method for preparing the aforementioned hole transport material is provided, the method comprising: step S1, under the protection of an inert gas, The raw materials are mixed and subjected to the first substitution reaction to generate Step S2, under the protection of inert gas, includes The raw materials of trimethylsilyl bromide and 1,4-dioxane are mixed and subjected to a first reaction to obtain an intermediate; step S3, under the protection of an inert gas, the raw materials including the intermediate, methanol and water are mixed and subjected to a second reaction to obtain Wherein, A is a heteroatom.

[0031] The raw material cost of the hole transport material is low, the process of preparing the hole transport material is simple, and it is suitable for industrial production. The hole transport material prepared by the above preparation method has good solubility, film forming property and hole mobility. This type of hole transport material has a deeper HOMO energy level that matches perovskite, and it can be used in perovskite solar cells without doping any additives, so that the perovskite solar cell has higher photoelectric conversion efficiency, photovoltaic performance and stability.

[0032] In order to further improve the solubility, film-forming property and hole mobility of the hole transport material, in one embodiment of the present application, in the above step S1, Each A in is independently O or S, optionally, for

[0033] In order to improve the reaction efficiency of the first substitution reaction and the yield of the product in step S1, in one embodiment of the present application, the raw materials in step S1 further include tetrakis(triphenylphosphine)palladium, potassium carbonate, toluene, ethanol and water; and / or, The molar ratio of potassium carbonate to tetrakis(triphenylphosphine)palladium is 1:2.2-2.5:4-6:0.05-0.1; and / or, the temperature of the first substitution reaction is 85-90° C.; and / or, the time of the first substitution reaction is 6-12 hours.

[0034] In one embodiment of the present application, the temperature of the first reaction is 25-30° C.; and / or, the time of the first reaction is 12-16 hours; and / or, the temperature of the second reaction is 25-30° C.; and / or, the time of the second reaction is 12-16 hours; and / or, The molar ratio of trimethylsilyl bromide to trimethylsilyl bromide is 1:10-20.

[0035] Controlling the temperature and time of the first reaction and the temperature and time of the second reaction helps to improve the reaction efficiency of the first reaction and the second reaction. The amount ratio of trimethylsilyl bromide to trimethylsilyl bromide within the above range is helpful to further improve the yield of the final product.

[0036] In order to further reduce the cost of raw materials, in one embodiment of the present application, the above The preparation method comprises: step S11, comprising After mixing with the raw material of N-bromosuccinimide, bromination reaction is carried out to obtain Step S12 includes The raw materials of tetrabutylammonium bromide, dibromobutane and potassium hydroxide are mixed and subjected to a second substitution reaction to obtain Step S13 includes After mixing with the raw material of triethyl phosphite, a third substitution reaction is carried out to obtain

[0037] To improve In one embodiment of the present application, the raw material in the above step S11 also includes tetrahydrofuran, The molar ratio of the amount of N-bromosuccinimide is 1:2.5-3; and / or, the temperature of the bromination reaction is 0-5°C; and / or, the time of the bromination reaction is 12-18h; and / or, in step S12, The molar ratio of tetrabutylammonium bromide to potassium hydroxide is 1:0.1-0.2:7-10; and / or, the temperature of the second substitution reaction is 65-85°C; and / or, the time of the second substitution reaction is 12-24h; and / or, in step S13, The molar ratio of the third substitution reaction to triethyl phosphite is 1:25-50; and / or the temperature of the third substitution reaction is 140-150° C.; and / or the time of the third substitution reaction is 12-24 hours.

[0038] In another typical embodiment of the present application, a perovskite solar cell is provided, such as Figure 3 As shown, it includes a transparent conductive layer 1, a hole transport layer 2, a perovskite layer 3, an electron transport layer 4 and an electrode layer 5, wherein the hole transport layer is composed of the aforementioned hole transport material.

[0039] Since the above-mentioned perovskite solar cell contains the hole transport material of the present application, the perovskite solar cell has higher photoelectric conversion efficiency, photovoltaic performance and stability.

[0040] Including but not limited to, the transparent conductive layer 1 is an ITO glass sheet, the perovskite layer 3 is (3FBA)2(MA)3Pb4I 13 composition (3FBA=3-fluorobenzylammonium, MA=methylammonium), the electron transport layer 4 is PC61BM, and the electrode layer 5 is a Cr / Au electrode.

[0041] The method for preparing the above-mentioned perovskite solar cell comprises the following steps:

[0042] (1) Cleaning of the transparent conductive layer 1: The ITO glass sheet was ultrasonically cleaned with deionized water, acetone and ethanol for 15 to 20 minutes in sequence, and then the residual solvent on the surface of the ITO was blown dry with a N2 air gun. The ITO glass sheet was then treated with oxygen plasma for 10 to 15 minutes, and then the ITO glass sheet was transferred to a nitrogen glove box.

[0043] (2) Preparation of hole transport layer 2: Weigh 3-15 mg of the hole transport material of the present application and completely dissolve it in 1 mL of chlorobenzene solution, take an appropriate amount of the solution and evenly drop it onto the ITO glass substrate, spin coat at 4000-5000 rpm for 20-30 seconds, and then anneal at 90-110° C. for 10 minutes;

[0044] (3) Preparation of perovskite layer 3: The ITO / hole transport layer substrate obtained above is cooled to room temperature, preheated at 130-140°C for 3-5 minutes, 50 μL of perovskite solution is spread over the ITO / hole transport layer substrate, spin coated at 3000-5000 rpm for 20-30 seconds, and then annealed at 90-100°C for 10 minutes to prepare a perovskite layer. The perovskite solution is prepared by mixing 3-bromo-benzyl-ammonium iodide or 3-chlorobenzyl ammonium iodide, methyl ammonium chloride, and lead iodide in a certain molar ratio in N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO);

[0045] (4) Preparation of electron transport layer 4: The ITO / hole transport layer / perovskite substrate obtained above was cooled to room temperature, PC61BM was prepared into a 15 mg / mL solution, and then 40 μL of the PC61BM solution was spread over the ITO / hole transport layer / perovskite substrate, and spin-coated at 1000 rpm for 30 to 50 seconds;

[0046] (5) Preparation of electrode layer 5: The above substrate is placed in a vacuum evaporation chamber, and Cr (6 nm) and Au (80 nm) are evaporated on the PC61BM layer respectively, thereby obtaining a perovskite solar cell.

[0047] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0048] Example 1

[0049] Synthesis of the compound of formula (2)

[0050]

[0051] In a 100mL round-bottomed flask, add the compound of formula (1) (0.89g, 4.24mmol) and tetrahydrofuran (10mL), then add N-bromosuccinimide (1.89g, 10.6mmol) to carry out substitution reaction, the reaction temperature is 0°C, and the reaction time is 12h. After the reaction is completed, water is used to quench the reaction, and dichloromethane is used for extraction. The organic layers are combined, dried over anhydrous magnesium sulfate, and then the organic solvent is removed by a rotary evaporator to obtain a crude product. With the main component and the eluent having a volume ratio of petroleum ether / dichloromethane = 10 / 1, flash column chromatography is used for further purification to obtain the compound of formula (2) as a white solid (1.40g, a yield of 90%).

[0052] Synthesis of compound of formula (3)

[0053]

[0054] In a 100mL double-necked bottle, add the compound of formula (2) (1.00g, 2.72mmol), tetrabutylammonium bromide (0.32g, 0.27mmol) dissolved in dibromobutane (15mL), then dropwise add 5mL of potassium hydroxide aqueous solution, wherein the amount of potassium hydroxide is 24mmol, carry out substitution reaction, reaction temperature is 65°C, reaction time is 12h. After the reaction is completed, water is used to quench the reaction, dichloromethane is used for extraction, the organic layers are combined, dried over anhydrous magnesium sulfate, and then the organic solvent is removed by rotary evaporator to obtain a crude product. With the main component and volume ratio of petroleum ether / dichloromethane = 10 / 1 eluent, flash column chromatography is used for further purification to obtain the compound of formula (3) as a colorless oil (1.20g, yield is 89%).

[0055] Synthesis of compound of formula (4)

[0056]

[0057] In a 100 mL double-necked flask, the compound of formula (3) (1.20 g, 2.39 mmol) and triethyl phosphite (60 mmol, 10 mL) were added and mixed, and then reacted under a nitrogen atmosphere at a reaction temperature of 140° C. for 12 h. After the reaction, the organic solvent was removed by a rotary evaporator to obtain a crude product of the compound of formula (4) (1.30 g, 2.27 mmol).

[0058] Synthesis of compound of formula (6)

[0059]

[0060] The compound of formula (5) (1.15 g, 3 mmol), 2-boric acid thiophene (0.46 g, 3.6 mmol), tetrakis(triphenylphosphine)palladium (0.092 g, 0.08 mmol), potassium carbonate (1.2 g, 9 mmol) were weighed and added to a 100 mL double-necked reaction flask, and DMF (40 mL) was used as solvent, and the reaction was carried out at 85° C. for 8 hours under N2 gas. The mixture was cooled to 25° C., extracted with dimethyl carbonate (DCM), the organic phase was dried with anhydrous Mg2SO4, filtered, and distilled under reduced pressure. Finally, after column chromatography, the volume ratio of petroleum ether (PE) to dimethyl carbonate was 12:1, and purified to obtain 0.84 g of green solid powder of the compound of formula (6), with a yield of 71%.

[0061] Synthesis of compound of formula (7)

[0062]

[0063] The compound of formula (6) (10 mmol) was weighed and added to a 500 mL three-necked flask, and then 30 mL of dry THF was added. The mixture was cooled to -78 °C under N2 conditions and stirred for 10 min. Then n-butyl lithium (3.75 mL, 1.00 equiv, 1.6 Minn-hexane) was slowly added dropwise, and the mixture was reacted at -78 °C for 1 hour. Then tert-butyl alcohol pinacol borate (2.75 mL, 15 mmol) was added, and the reaction was continued at -78 °C for 1 hour. Finally, the mixture was moved to 25 °C for 12 hours. The reaction was quenched with 50 mL of deionized water, extracted with saturated NaCl solution and DCM, and the organic phase was dried over anhydrous Mg2SO4, filtered, and finally purified by column chromatography. The volume ratio of petroleum ether (PE) to dimethyl carbonate was 15:1 to obtain the compound of formula (7).

[0064] Synthesis of compound of formula (8)

[0065]

[0066]

[0067] In a 100 mL double-necked flask, the compound of formula (4) (0.58 g, 1 mmol), the compound of formula (7) (2.2 mmol), tetrakis(triphenylphosphine)palladium (57 mg, 0.05 mmol), potassium carbonate (0.83 g, 6 mmol) were added, and the solvent was toluene, ethanol and water (volume ratio was 2:1:1), and the reaction was carried out at 85° C. for 6 hours. After cooling to 25° C., the mixture was extracted with DCM, the organic phase was dried over anhydrous Mg2SO4, filtered, and distilled under reduced pressure. Finally, after column chromatography, the volume ratio of petroleum ether (PE) and dimethyl carbonate was 4:1, and the compound of formula (7) (0.75 g, 0.74 mmol) was purified, and the yield was 75%.

[0068] Synthesis of 4PAAc-OMe

[0069]

[0070] In a 100mL double-necked flask, add the compound of formula (8) (2mmol) to anhydrous 1,4-1,4-dioxane (10mL) at 25°C, add trimethylsilyl bromide (3.06g, 20mmol), and then stir for 12h. Remove 1,4-dioxane with a rotary evaporator to obtain a solid powder. Dissolve the solid powder in methanol (10mL) at 25°C, then add deionized water dropwise until the mixture becomes opaque, and stir for another 12 hours. The crude product is collected by filtration and washed with deionized water. The crude product is dissolved in tetrahydrofuran (THF) (5mL), reprecipitated in acetone (20mL), and filtered to obtain the final product 4PAAc-OMe (1.2g, yield 75%). The hydrogen nuclear magnetic resonance spectrum of 4PAAc-OMe is shown as follows Figure 1 shown.

[0071] Example 2

[0072] Synthesis of the compound of formula (2)

[0073]

[0074] In a 100mL round-bottomed flask, add the compound of formula (1) (0.89g, 4.24mmol) and tetrahydrofuran (10mL), then add N-bromosuccinimide (1.89g, 10.6mmol) to carry out substitution reaction, the reaction temperature is 0°C, and the reaction time is 12h. After the reaction is completed, water is used to quench the reaction, and dichloromethane is used for extraction. The organic layers are combined, dried over anhydrous magnesium sulfate, and then the organic solvent is removed by a rotary evaporator to obtain a crude product. With the main component and the eluent having a volume ratio of petroleum ether / dichloromethane = 10 / 1, flash column chromatography is used for further purification to obtain the compound of formula (2) as a white solid (1.40g, yield 90%).

[0075] Synthesis of compound of formula (3)

[0076]

[0077] In a 100mL double-necked bottle, add the compound of formula (2) (1.00g, 2.72mmol), tetrabutylammonium bromide (0.32g, 0.27mmol) dissolved in dibromobutane (15mL), then dropwise add 5mL of potassium hydroxide aqueous solution, wherein the amount of potassium hydroxide is 24mmol, carry out substitution reaction, reaction temperature is 65°C, reaction time is 12h. After the reaction is completed, water is used to quench the reaction, dichloromethane is used for extraction, the organic layers are combined, dried over anhydrous magnesium sulfate, and then the organic solvent is removed by rotary evaporator to obtain a crude product. With the main component and volume ratio of petroleum ether / dichloromethane = 10 / 1 eluent, flash column chromatography is used for further purification to obtain the compound of formula (3) as a colorless oil (1.20g, yield 89%).

[0078] Synthesis of compound of formula (4)

[0079]

[0080] In a 100 mL double-necked flask, the compound of formula (3) (1.20 g, 2.39 mmol) and triethyl phosphite (60 mmol, 10 mL) were added and mixed, and then reacted under a nitrogen atmosphere at a reaction temperature of 140° C. for 12 h. After the reaction, the organic solvent was removed by a rotary evaporator to obtain a crude product of the compound of formula (4) (1.30 g, 2.27 mmol).

[0081] Synthesis of compound of formula (11)

[0082]

[0083] The compound of formula (10) (1.15 g, 3 mmol), 2-boric acid thiophene (0.46 g, 3.6 mmol), tetrakis(triphenylphosphine)palladium (0.092 g, 0.08 mmol), potassium carbonate (1.2 g, 9 mmol) were weighed and added to a 100 mL two-necked reaction flask, and DMF (40 mL) was used as solvent, and the reaction was carried out at 85° C. for 8 hours under N2 gas. The mixture was cooled to 25° C., extracted with DCM, the organic phase was dried over anhydrous Mg2SO4, filtered, and distilled under reduced pressure. Finally, it was purified by column chromatography with a volume ratio of petroleum ether (PE) and dimethyl carbonate of 12:1 to obtain 0.87 g of solid powder of the compound (11), with a yield of 71%.

[0084] Synthesis of compound of formula (12)

[0085]

[0086] The compound of formula (11) (10 mmol) was weighed and added to a 500 mL three-necked flask, and then 30 mL of dry THF was added. The mixture was cooled to -78 ° C. and stirred for 10 min under N2 conditions. Then, n-butyl lithium (3.75 mL, 1.00 equiv, 1.6 Min-hexane) was slowly added dropwise, and the mixture was reacted at -78 ° C. for 1 hour. Then, tert-butyl alcohol pinacol borate (2.75 mL, 15 mmol) was added, and the reaction was continued at -78 ° C. for 1 hour, and finally, the mixture was moved to 25 ° C. for 12 hours. The reaction was quenched with 50 mL of deionized water, extracted with saturated NaCl solution and DCM, and the organic phase was dried over anhydrous Mg2SO4, filtered, and finally purified by column chromatography. The volume ratio of petroleum ether (PE) to dimethyl carbonate was 15:1, and the compound of formula (12) was obtained.

[0087] Synthesis of compound of formula (13)

[0088]

[0089]

[0090] In a 100 mL double-necked flask, the compound of formula (4) (0.58 g, 1 mmol), the compound of formula (7) (2.2 mmol), tetrakis(triphenylphosphine)palladium (57 mg, 0.05 mmol), potassium carbonate (0.83 g, 6 mmol) were added, and the solvent was toluene, ethanol and water (volume ratio was 2:1:1), and the reaction was carried out at 85°C for 6 hours. After cooling to 25°C, the mixture was extracted with DCM, the organic phase was dried over anhydrous Mg2SO4, filtered, and distilled under reduced pressure, and finally purified by column chromatography, and the volume ratio of petroleum ether (PE) and dimethyl carbonate was 4:1 to obtain the compound of formula (13) (0.75 g, 0.71 mmol), with a yield of 70%.

[0091] Synthesis of 4PAAc-SMe

[0092]

[0093] In a 100mL double-necked flask, add the compound of formula (13) (g, 2mmol) to anhydrous 1,4-1,4-dioxane (10mL) at 25°C, add trimethylsilyl bromide (3.06g, 20mmol), and then stir overnight. Remove 1,4-dioxane with a rotary evaporator to obtain a solid powder. Dissolve the solid powder in methanol (10mL) at 25°C, then add deionized water dropwise until the mixture becomes opaque, and stir for another 12 hours. The crude product is collected by filtration and washed with deionized water. The crude product is dissolved in THF (5mL), reprecipitated in acetone (20mL), and filtered to obtain the final product 4PAAc-SMe (1.2g, yield 75%). The hydrogen nuclear magnetic resonance spectrum of 4PAAc-SMe is shown as follows Figure 2 shown.

[0094] Example 3

[0095] The difference from Example 1 is that, in a 100mL round-bottomed bottle, compound (1) (3.53mmol) and tetrahydrofuran (10mL) are added, and then N-bromosuccinimide (1.89g, 10.6mmol) is added to carry out substitution reaction, the temperature of substitution reaction is 5°C, and the time of substitution reaction is 18h. After the reaction is completed, water quenching reaction is adopted, and dichloromethane is extracted, and the organic layers are combined, dried over anhydrous magnesium sulfate, and then the organic solvent is removed by rotary evaporator to obtain a crude product. With the main component and eluent of petroleum ether / dichloromethane=10 / 1 in volume ratio, flash column chromatography is adopted to carry out further purification, and compound (2) is obtained as a white solid (1.16g, and the yield is 89%).

[0096] Example 4

[0097] The difference from Example 1 is that, in a 100mL round-bottomed bottle, compound (2.65mmol) of formula (1) and tetrahydrofuran (10mL) are added, and then N-bromosuccinimide (1.89g, 10.6mmol) is added to carry out substitution reaction, the temperature of substitution reaction is 6°C, and the time of substitution reaction is 20h. After the reaction is completed, water quenching reaction is adopted, and dichloromethane is extracted, and the organic layers are combined, dried over anhydrous magnesium sulfate, and then the organic solvent is removed by rotary evaporator to obtain a crude product. With the main component and eluent of petroleum ether / dichloromethane=10 / 1 in volume ratio, flash column chromatography is adopted to carry out further purification, and compound (2) is obtained as a white solid (0.78g, and the yield is 81%).

[0098] Example 5

[0099] The difference from Example 1 is that the compound of formula (2) (1.00 g, 2.72 mmol) is added to a 100 mL double-necked bottle, tetrabutylammonium bromide (0.54 mmol) is dissolved in dibromobutane (15 mL), and then added dropwise to 5 mL of potassium hydroxide aqueous solution, wherein the amount of potassium hydroxide is 19.04 mmol, and a substitution reaction is carried out, the reaction temperature is 85 ° C, and the reaction time is 24 h. After the reaction is completed, water is used to quench the reaction, and dichloromethane is used for extraction. The organic layers are combined, dried over anhydrous magnesium sulfate, and then the organic solvent is removed by a rotary evaporator to obtain a crude product. With the main component and the eluent having a volume ratio of petroleum ether / dichloromethane = 10 / 1, flash column chromatography is used for further purification to obtain the compound of formula (3) as a colorless oil (1.18 g, a yield of 87%).

[0100] Example 6

[0101] The difference from Example 1 is that the compound of formula (2) (1.00 g, 2.72 mmol) is added to a 100 mL double-necked bottle, tetrabutylammonium bromide (0.14 mmol) is dissolved in dibromobutane (15 mL), and then added dropwise to 5 mL of potassium hydroxide aqueous solution, wherein the amount of potassium hydroxide is 16.32 mmol, and a substitution reaction is carried out, the reaction temperature is 90 ° C, and the reaction time is 25 h. After the reaction is completed, water is used to quench the reaction, and dichloromethane is used for extraction. The organic layers are combined, dried over anhydrous magnesium sulfate, and then the organic solvent is removed by a rotary evaporator to obtain a crude product. With the main component and the eluent having a volume ratio of petroleum ether / dichloromethane = 10 / 1, flash column chromatography is used for further purification to obtain the compound of formula (3) as a colorless oil (0.68 g, a yield of 50%).

[0102] Example 7

[0103] The difference from Example 1 is that the compound of formula (3) (1.20 g, 2.39 mmol) and triethyl phosphite (119.5 mmol) are added to a 100 mL double-necked flask and mixed, and then reacted under a nitrogen atmosphere at a reaction temperature of 150° C. for 24 h. After the reaction is completed, the organic solvent is removed by a rotary evaporator to obtain a crude product of the compound of formula (4) (1.28 g, 2.24 mmol).

[0104] Example 8

[0105] The difference from Example 1 is that the compound of formula (3) (1.20 g, 2.39 mmol) and triethyl phosphite (47.8 mmol) are added to a 100 mL double-necked bottle and mixed, and then reacted under a nitrogen atmosphere at a reaction temperature of 130° C. for 10 h. After the reaction is completed, the organic solvent is removed by a rotary evaporator to obtain a crude product of the compound of formula (4) (0.93 g, 1.62 mmol).

[0106] Example 9

[0107] The difference from Example 1 is that the compound of formula (4) (1 mmol), the compound of formula (7) (2.5 mmol), tetrakis(triphenylphosphine)palladium (0.1 mmol), and potassium carbonate (4 mmol) are added to a 100 mL double-necked flask, and the solvent is toluene, ethanol and water (volume ratio is 2:1:1), and the reaction is carried out at 90° C. for 12 hours. The mixture is cooled to 25° C., extracted with DCM, the organic phase is dried over anhydrous Mg2SO4, filtered, and distilled under reduced pressure. Finally, after column chromatography, the volume ratio of petroleum ether (PE) and dimethyl carbonate is 4:1, and the compound of formula (7) (0.86 g, yield is 74%) is obtained.

[0108] Example 10

[0109] The difference from Example 1 is that the compound of formula (4) (1 mmol), the compound of formula (7) (2 mmol), tetrakis(triphenylphosphine)palladium (0.2 mmol), and potassium carbonate (3 mmol) are added to a 100 mL double-necked flask, and the solvent is toluene, ethanol and water (volume ratio is 2:1:1), and the reaction is carried out at 80° C. for 5 hours. The mixture is cooled to 25° C., extracted with DCM, the organic phase is dried over anhydrous Mg2SO4, filtered, and distilled under reduced pressure. Finally, after column chromatography, the volume ratio of petroleum ether (PE) and dimethyl carbonate is 4:1, and the compound of formula (7) (0.53 g, yield is 45%) is purified.

[0110] Embodiment 11

[0111] The difference from Example 1 is that the compound of formula (8) (1 mmol) is added to a 100 mL double-necked flask in anhydrous 1,4-1,4-dioxane (10 mL) at 30°C, trimethylsilane bromide (3.06 g, 20 mmol) is added dropwise, and then stirred for 16 hours. 1,4-dioxane is removed by a rotary evaporator to obtain a solid powder. The solid powder is dissolved in methanol (10 mL) at 30°C, and then deionized water is added dropwise until the mixture becomes opaque and stirred for another 16 hours. The crude product is collected by filtration and washed with deionized water. The crude product is dissolved in tetrahydrofuran (THF) (5 mL), reprecipitated in acetone (20 mL), and filtered to obtain the final product 4PAAc-OMe (0.83 g, yield 73%).

[0112] Example 12

[0113] The difference from Example 1 is that the compound of formula (8) (0.9 mmol) is added to anhydrous 1,4-1,4-dioxane (10 mL) at 40°C in a 100 mL double-necked flask, trimethylsilane bromide (3.06 g, 20 mmol) is added dropwise, and then stirred for 10 hours. 1,4-dioxane is removed by a rotary evaporator to obtain a solid powder. The solid powder is dissolved in methanol (10 mL) at 40°C, and then deionized water is added dropwise until the mixture becomes opaque and stirred for another 10 hours. The crude product is collected by filtration and washed with deionized water. The crude product is dissolved in tetrahydrofuran (THF) (5 mL), reprecipitated in acetone (20 mL), and filtered to obtain the final product 4PAAc-OMe (0.7 g, yield 62%).

[0114] Embodiment 13

[0115] The 4PAAc-OMe prepared in Example 1 is used as a hole transport layer of a perovskite solar cell. The structure of the perovskite solar cell is as follows: Figure 3 As shown, from bottom to top are a transparent conductive layer 1 (ITO glass), a hole transport layer 2 (4PAAc-OMe), a perovskite layer 3, an electron transport layer 4 (PC61BM) and an electrode 5 (Cr / Au). The preparation method of a perovskite solar cell includes the following steps:

[0116] (1) Cleaning of the transparent conductive layer 1: The ITO glass sheet was ultrasonically cleaned with deionized water, acetone and ethanol for 15 minutes in sequence, and then the residual solvent on the surface of the ITO was blown dry with a N2 air gun, followed by an oxygen plasma treatment for 10 minutes, and then the ITO glass sheet was transferred to a nitrogen glove box;

[0117] (2) Preparation of hole transport layer 2: 15 mg of 4PAAc-OMe was weighed and completely dissolved in 1 mL of chlorobenzene solution, and the solution was evenly dropped onto the ITO glass substrate, spin-coated at 4000 rpm for 20 seconds, and then annealed at 110° C. for 10 minutes;

[0118] (3) Preparation of perovskite layer 3: The ITO / hole transport layer substrate obtained above was cooled to room temperature, preheated at 130°C for 3 minutes, 50 μL of perovskite solution was taken to cover the ITO / hole transport layer substrate, spin coated at 3000 rpm for 20 seconds, and then annealed at 100°C for 10 minutes to prepare a perovskite layer. The perovskite solution was prepared by mixing 3-fluorobenzylammonium, methylammonium, and lead iodide in a molar ratio of 2.2:3.5:4 in a solution of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 4:1;

[0119] (4) Preparation of electron transport layer 4: The ITO / hole transport layer / perovskite substrate obtained above was cooled to room temperature, PC61BM was prepared into a 15 mg / mL solution, and then 40 μL of the PC61BM solution was spread over the ITO / hole transport layer / perovskite substrate, and spin-coated at 1000 rpm for 30 seconds;

[0120] (5) Preparation of electrode layer 5: The above substrate is placed in a vacuum evaporation chamber, and Cr (6 nm) and Au (80 nm) are evaporated on the PC61BM layer respectively, thereby obtaining a perovskite solar cell.

[0121] Embodiment 14

[0122] The difference from Example 13 is that 4PAAc-SMe is used to replace 4PAAc-OMe, and a perovskite solar cell is finally obtained.

[0123] Comparative Example 1

[0124] The difference from Example 13 is that 2BrDMAcPA prepared in Example 1 of Chinese patent application with patent application publication number CN116178430A is used to replace 4PAAc-OMe, and finally a perovskite solar cell is obtained.

[0125] The decomposition temperature, HOMO energy level and hole mobility of 4PAAc-OMe prepared in Example 1 and 4PAAc-SMe prepared in Example 2 were tested. The test results are shown in Table 1.

[0126] The perovskite solar cells prepared in the above-mentioned Example 13, Example 14 and Comparative Example 1 were tested for photoelectric conversion efficiency, open circuit voltage, short circuit current and fill factor. The test results are shown in Table 2.

[0127] Table 1

[0128]

[0129] Table 2

[0130]

[0131] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0132] The present application introduces thiophene-methoxy triphenylamine groups and thiophene-methylthio triphenylamine groups into acridine phosphate side chains to provide a series of novel hole transport materials, which have good solubility in solvents such as dimethyl sulfoxide, N,N' dimethylformamide, toluene, chlorobenzene and dichloromethane. The material has good film-forming properties, and has good wettability with perovskite precursor solvents, thereby helping to improve the crystallinity and film-forming properties of perovskite. And this type of hole transport material has a higher decomposition temperature, better thermal stability and higher hole mobility, which is conducive to the extraction and transmission of holes. This type of hole transport material has a deeper HOMO energy level that matches perovskite, and it can be used in perovskite solar cells without doping any additives, so that perovskite solar cells have higher photoelectric conversion efficiency, photovoltaic performance and stability, and the material has repeatability.

[0133] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A hole transport material, characterized in that: The chemical structural formula of the hole transport material is wherein each A is independently a heteroatom.

2. The hole transport material according to claim 1, characterized in that Each of the A's is independently O or S.

3. The hole transport material according to claim 1 or 2, characterized in that The decomposition temperature of the hole transport material is 298 to 345° C.; and / or the HOMO energy level of the hole transport material is -5.39 to -5.32 eV; and / or the hole mobility of the hole transport material is 3.67×10 -4 ~6.35×10 -4 cm 2 ·V -1 ·S -1 .

4. A method for preparing a hole transport material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, under the protection of inert gas, includes and The raw materials are mixed and subjected to the first substitution reaction to generate Step S2, under the protection of inert gas, includes The raw materials of trimethylsilyl bromide and 1,4-dioxane are mixed and subjected to a first reaction to obtain an intermediate; Step S3, under the protection of inert gas, mixing the raw materials including the intermediate, methanol and water and performing a second reaction to obtain Wherein, A is a heteroatom.

5. The preparation method according to claim 4, characterized in that: In the step S1, the Each A in is independently O or S.

6. The preparation method according to claim 4 or 5, characterized in that: The raw materials in step S1 further include tetrakis(triphenylphosphine)palladium, potassium carbonate, toluene, ethanol and water; and / or, Said The molar ratio of the potassium carbonate to the tetrakis(triphenylphosphine)palladium is 1:2.2-2.5:4-6:0.05-0.1; and / or the temperature of the first substitution reaction is 85-90°C; and / or the time of the first substitution reaction is 6-12h.

7. The preparation method according to claim 4 or 6, characterized in that: The temperature of the first reaction is 25 to 30°C; and / or, the time of the first reaction is 12 to 16 hours; and / or, the temperature of the second reaction is 25 to 30°C; and / or, the time of the second reaction is 12 to 16 hours; and / or, The molar ratio of the amount of trimethylsilyl bromide to the trimethylsilyl bromide is 1:10-20.

8. The preparation method according to any one of claims 4 to 7, characterized in that Said The preparation method comprises: Step S11 includes After mixing with the raw material of N-bromosuccinimide, bromination reaction is carried out to obtain Step S12 includes the The raw materials of tetrabutylammonium bromide, dibromobutane and potassium hydroxide are mixed and subjected to a second substitution reaction to obtain Step S13 includes the After mixing with the raw material of triethyl phosphite, a third substitution reaction is carried out to obtain the 9. The preparation method according to claim 8, characterized in that: The raw material in step S11 also includes tetrahydrofuran, The molar ratio of the N-bromosuccinimide is 1:2.5-3; and / or the temperature of the bromination reaction is 0-5°C; and / or the time of the bromination reaction is 12-18h; And / or, in step S12, the The molar ratio of the tetrabutylammonium bromide to the potassium hydroxide is 1:0.1-0.2:7-10; and / or the temperature of the second substitution reaction is 65-85° C.; and / or the time of the second substitution reaction is 12-24 hours; And / or, in step S13, the The molar ratio of the triethyl phosphite to the triethyl phosphite is 1:25-50; and / or, the temperature of the third substitution reaction is 140-150° C.; and / or, the time of the third substitution reaction is 12-24 hours.

10. A perovskite solar cell comprising a transparent conductive layer, a hole transport layer, a perovskite layer, an electron transport layer and an electrode layer, characterized in that: The hole transport layer is composed of the hole transport material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Hole transport material taking benzodithiophene diketone as core, synthesis method and application of hole transport material in perovskite solar cell

    CN111909169A

  • Hole-transporting self-organised monolayer for perovskite solar cells

    CN112469727A

  • Carbazole small organic molecule hole transport material containing phosphonic acid and methylthio group, and preparation method and application of carbazole small organic molecule hole transport material

    CN115819457A

  • Self-assembly hole selection material based on acridine and preparation method and application thereof

    CN116178430A

  • Hole transport material, preparation method thereof and perovskite solar cell

    CN118955562A

Cited By

  • Carbazole phosphate material as well as preparation method and application thereof

    CN119504858A

  • Phosphoric acid carbazole-based material, method for preparing the same, and use thereof

    CN119504858B

  • Self-assembled molecular material and application

    CN122127365A